The Role of Civics Teachers as Evaluators in Improving Student Learning Discipline - Rizka Aulya Hasanah (International Journal of Students Education, 2024)
This research aims to determine the extent of the role of PPKn teachers as evaluators in building and improving the character of students' learning discipline. The method used in this research is a systematic literature review which is carried out by collecting, critically evaluating, integrating and presenting findings from various research studies on research questions or topics of interest. The author uses 8 published articles as sources. The articles used are articles that have previously been filtered based on their suitability to themes that can answer the problems in this research. Based on the research results, it can be seen that the role of PPKn teachers is not only to deliver material in class, but PPKn teachers also play a role in improving the character of students' learning discipline. This is done by PPKn teachers applying rules in teaching and learning activities in class and then conducting evaluations if students have not demonstrated success in implementing learning discipline. The recommendations in this research are aimed at school principals, teachers and parents with a purpose Students increase their disciplinary behavior in obeying the rules at school or in the classroom when studying.